2007
DOI: 10.1002/eat.20434
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen for binge eating: An open‐label trial

Abstract: In this open-label trial, baclofen was associated with decreased binge eating frequency in patients with BED and BN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 36 publications
3
57
1
1
Order By: Relevance
“…Currently, atomoxetine, fluoxetine, topiramate, and baclophen have demonstrated limited efficacy in clinical studies for BED (McElroy et al, 2007a,b;Broft et al, 2007;Grilo et al, 2012). The present work demonstrated that, in preclinical models, the novel NOP receptor antagonist LY2940094 effectively inhibited feeding behavior.…”
Section: Discussionmentioning
confidence: 52%
“…Currently, atomoxetine, fluoxetine, topiramate, and baclophen have demonstrated limited efficacy in clinical studies for BED (McElroy et al, 2007a,b;Broft et al, 2007;Grilo et al, 2012). The present work demonstrated that, in preclinical models, the novel NOP receptor antagonist LY2940094 effectively inhibited feeding behavior.…”
Section: Discussionmentioning
confidence: 52%
“…Recent studies also reported that baclofen was effective to treat binge-eating of fat in animals (14) as well as binge-eating in humans (15), the mechanisms of which have been postulated to be similar to drug abuse (14). While we have not examined changes in the desire for fat exclusively, the desire to take sweets evaluated by a visual analogue scale was decreased by baclofen in this study.…”
Section: Discussionmentioning
confidence: 53%
“…[36][37][38][39][40] Preclinical, phenomenologic, and comorbidity data suggest binge eating disorder and substance use disorders are related 2,41,42 and growing research shows that medications that reduce craving and consumption of drugs of abuse 43 may also reduce binge eating. 8,9,15,44,45 Indeed, one such drug, baclofen, shares a common mechanism with sodium oxybate-agonism of centrally active GABA-B receptors. 45 Finally, sodium oxybate is well tolerated when taken as prescribed.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,15,44,45 Indeed, one such drug, baclofen, shares a common mechanism with sodium oxybate-agonism of centrally active GABA-B receptors. 45 Finally, sodium oxybate is well tolerated when taken as prescribed. 16,17,24 Compared with the antidepressants, antiepileptics, and antiobesity agents presently used in binge eating disorder, sodium oxybate is associated with lower rates of sexual dysfunction, cognitive impairment, and hypertension, respectively.…”
Section: Introductionmentioning
confidence: 99%